2013
DOI: 10.1055/s-0032-1325524
|View full text |Cite
|
Sign up to set email alerts
|

Wie sicher ist die Sedierung in der gastrointestinalen Endoskopie? Eine multizentrische Auswertung von 388 404 Endoskopien und Auswertung der Daten aus prospektiv geführten Komplikationsregistern von Mitgliedern der Arbeitsgemeinschaft leitender Gastroenterologen im Krankenhaus (ALGK)

Abstract: Including nearly 400,000 endoscopies, this study represents the largest prospective, multicenter record of the complications of sedation worldwide. The analysis shows that sedation is carried out safely in gastrointestinal endoscopy. The morbidity and mortality rates are much lower than previously reported in the literature in similar groups of patients. Risk factors for the occurrence of serious complications include emergency examinations and patients in ASA class ≥ 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“… 2 , 30 Despite numerous studies demonstrating the safety of endoscopic sedation, especially EDP, most results were obtained from randomized controlled trials or large nonrandomized case series, rather than a real-life clinical setting. 1 , 6 10 , 27 , 28 In this regard, our current findings suggest that the incidence of serious respiratory events during endoscopic sedation is underestimated in real-life settings. In fact, the proportion of endoscopists who had experience in serious respiratory events in this study was much higher than our expectations.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“… 2 , 30 Despite numerous studies demonstrating the safety of endoscopic sedation, especially EDP, most results were obtained from randomized controlled trials or large nonrandomized case series, rather than a real-life clinical setting. 1 , 6 10 , 27 , 28 In this regard, our current findings suggest that the incidence of serious respiratory events during endoscopic sedation is underestimated in real-life settings. In fact, the proportion of endoscopists who had experience in serious respiratory events in this study was much higher than our expectations.…”
Section: Discussionmentioning
confidence: 66%
“… 1 , 2 , 5 , 6 , 27 , 28 In addition, there is accumulating evidence that EDP can be used safely and effectively for healthy individuals in elective GI endoscopy. 6 10 , 27 , 28 A recent large prospective study evaluating 10,000 patients who underwent endoscopic procedures also confirmed that EDP in an outpatient setting is a safe procedure among patients without severe comorbidities. 9 Given the different practice settings among countries, we believe that a future prospective cohort study is required to evaluate the safety of EDP in Korea.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Randomisierte Studien zu dieser Fragestellung liegen aber bis heute nicht vor, die ganz weit überwiegende Zahl aller Studien zum Thema „NAPS“ (> 95 %) wurde in einer „3-Mann-Situation“ vorgenommen. Dass die bundesdeutsche Anwendungswirklichkeit, wie in einer Erhebung von A. Behrens et al 410 gezeigt, die Beteiligung einer „dritten Person“ nur in maximal 50 % der Fälle realisiert, ist für die Empfehlung einer Leitlinie (die sich primär an der publizierten Evidenz und der Anwendungssicherheit orientieren muss) unerheblich. Direkt vergleichende, randomisierte Studien zur Frage der Komplikationshäufigkeit bei Vorgehen mittels „2-Mann- vs. 3-Mann-Prozedur“ im Rahmen der Sedierung bei der GI-Endoskopie fehlen bisher.…”
Section: Leitlinie – Strukturqualitätunclassified
“…This could be proven by the analysis of a prospective complication registry of 388,404 gastrointestinal endoscopic procedures in the typical NAAP manner [11,12]. In this context the study by Müller et al [13] should be seen.…”
mentioning
confidence: 99%